-Attitudes of Public Relations Practitioners Towards Professional Ethics and their Relation to the Performance Level- A Comparative Study between the Public and Private Sectors - Al-Silme, Manal (Journal of Humanities & Social Sciences, 2019)
The aim of this study is to identify trends in public relations practitioners in the public and private sectors towards ethics in light of the six dimensions (PR practitioner ethics towards itself as professional, and some colleagues, some internal and external audiences are, and about his organization and about the media, and on the Internet) and their relationship to performance, the study adopted survey methodology and questionnaire designed for this purpose, and has been applied to the study sample consisted of (97) alone from the public sector public relations practitioners, and (56) alone, public relations practitioners from the private sector, and the total sample (153 Single). The results of the study showed that public relations practitioners ’ responses in the public and private sectors towards themes of study (ethics dimension- level performance) came with degrees OK, with arithmetic ethics axis dimensions in the public sector (3.97 out of 5) in the private sector (3.95 out of 5), and the arithmetic of public- sector performance level axis (3.95 out of 5) in the private sector (3.86 out of 5) and it turns out the lack of statistically significant differences in trends study sample members around themes of study (ethics dimension- level performance) with different variable employment sector, as the results indicated that there was a correlation function statistically between trends toward ethics and performance in The public and private sectors, based on the results presented a set of recommendations, notably the enactment and implementation of rules and laws that help PR practitioners on perfect ethics and commitment to achieving good performance.